Addiction and devotion in early modern England - Lemon, Rebecca, 1968- (University of Pennsylvania Press, 2018)
Rebecca Lemon shows how sixteenth-century writers, such as Marlowe and Shakespeare, depict addiction in many forms, including to God, study, love, friendship, and drinking. Addiction and Devotion in Early Modern England explores the fine line between devotion and pathology, revealing addiction's laudable as well as pejorative meanings.
Keywords: Compulsive behavior in literature.; English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism.; English drama -- 17th century -- History and criticism.; Devotion in literature.; Alcoholism in literature.; Compulsive behavior -- England -- History -- 16th century.; Compulsive behavior -- England -- History -- 17th century.; Alcoholism -- England -- History -- 16th century.; Alcoholism -- England -- History -- 17th century.; Théâtre anglais -- 16e siècle -- Histoire et critique.; Théâtre anglais -- 17e siècle -- Histoire et critique.; Dévotion dans la littérature.; Alcoolisme dans la littérature.; Comportement compulsif -- Angleterre -- Histoire -- 16e siècle.; Comportement compulsif -- Angleterre -- Histoire -- 17e siècle.; Alcoolisme -- Angleterre -- Histoire -- 16e siècle.; Alcoolisme -- Angleterre -- Histoire -- 17e siècle.; DRAMA -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- Renaissance.; Alcoholism; Alcoholism in literature; Compulsive behavior; Compulsive behavior in literature; Devotion in literature; English drama; English drama -- Early modern and Elizabethan; England; 1500-1699; Criticism, interpretation, etc.; History